THE TOURISM DEVELOPMENT POLICY IN BANDUNG REGENCY: A STUDY ON KAMPUNG GAMIS– SOREANG - Saekul Anwar; Endang Wirjatmi Trilestari; Iin Agustina (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
This study aims to analyze the development of tourism destinations in Kampung Gamis Soreang by studying the socio-material relationships that underlie the development process. This study employed a qualitative approach to answer the research objectives. The data collection techniques were carried out by interviews, field observations and document analysis to answer research questions. The sampling was done by purposive sampling involving the Bandung Regency government and the local community of Kampung Gamis. The analytical framework developed describes the socio-techno-economic interaction of the surrounding actors with Kampung Gamis to obtain possible outcomes. The findings showed that there are at least four main actors in the stakeholder analysis of the tourism destination of Kampung Gamis, Soreang District, Bandung Regency; they are the government, associations or local tourism communities, entrepreneurs, and the local community. There are also some identified potentials in the development of Kampung Gamis as Tourism Destinations and several important obstacles such as lack of experience of business actors in the tourism destination of Kampung Gamis. Finally, pattern of actor and network relations in Kampung Gamis Tourism Destinations development reflects how crucial the development of kampung gamis is.